Implementation of Virgin Coconut Oil Moist Dressing in Diabetic Ulcer Wound Care: A Nursing Case Study - Bella Oktavera; Ade Fitriani; Lilis Lismayanti; Ayu Endang Purwati (KIAN JOURNAL, 2026)
Introduction: Diabetic ulcers are one of the most common chronic complications of Diabetes Mellitus and are associated with delayed wound healing, increased infection risk, and lower quality of life. Maintaining an optimal moist wound environment is an essential component of diabetic ulcer management. Virgin Coconut Oil (VCO) has antimicrobial, anti-inflammatory, and moisturizing properties that may enhance wound healing. Objective: To describe the implementation of Virgin Coconut Oil as a moist dressing in promoting diabetic ulcer wound healing through a nursing care approach. Method: This descriptive case study involved one patient with Type 2 Diabetes Mellitus presenting with a diabetic ulcer. Nursing care was provided through assessment, diagnosis, intervention, implementation, and evaluation according to the Indonesian Nursing Standards (SDKI, SIKI, and SLKI). Virgin Coconut Oil was applied as a moist dressing during three consecutive nursing visits. Wound progress was evaluated using clinical observations based on wound moisture, redness, signs of infection, and tissue appearance. Result: Progressive improvement was observed following three applications of VCO. The wound demonstrated improved moisture balance, reduced periwound redness, healthy granulation tissue formation, and no clinical signs of infection. These findings indicate that VCO supported the wound healing process during nursing care. Conclusion: Virgin Coconut Oil may serve as a practical, safe, and low-cost complementary intervention for diabetic ulcer wound management. Further studies involving larger samples and controlled study designs are recommended to confirm its effectiveness.